The parallax effect and magnification on daily orthopedic trauma radiographs - Gulini, Bruno Dada (2024)
Objective: To identify the parallax effect on radiographs of upper and lower limbs in everyday orthopedics. Methods: This was an experimental, descriptive-theoretical study, with data analysis of digital radiographs from a tertiary trauma hospital in southern Brazil. Results: The parallax effect and magnification recorded different degrees of deformation, in the analysis of radiographs of the upper limbs, the AP radiograph of the shoulder showed greater degrees of distortion at a predetermined point (4.00%), in lower limbs the pelvis showed a greater degree of magnification (7.85%). Conclusions: There was a positive association between image magnification and the size of the film or structure to be analyzed. The parallax effect has a significant impact on image distortion in the context of orthopedic trauma. Level of Evidence III.